2017
DOI: 10.1016/j.eururo.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair in Prostate Cancer: Biology and Clinical Implications

Abstract: Key literature on how genomic defects in the DNA damage repair pathway are relevant for prostate cancer biology and clinical management is reviewed. Potential implications for future changes in patient care are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(175 citation statements)
references
References 77 publications
3
154
0
10
Order By: Relevance
“…In this sample, patients with germline BRCA1/2 mutations had a 23% local failure rate in contrast to only 7% among non-carriers. [4] Other studies have corroborated the association between increased aggressiveness and germline BRCA1/2 lesions; these patients present with higher Gleason scores, have shorter metastasis-free survival and reduced overall survival compared to non-carriers. [57] Such patients therefore represent an unmet medical need.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this sample, patients with germline BRCA1/2 mutations had a 23% local failure rate in contrast to only 7% among non-carriers. [4] Other studies have corroborated the association between increased aggressiveness and germline BRCA1/2 lesions; these patients present with higher Gleason scores, have shorter metastasis-free survival and reduced overall survival compared to non-carriers. [57] Such patients therefore represent an unmet medical need.…”
Section: Introductionmentioning
confidence: 94%
“…In this context, if HR was also deficient then non-homologous end joining would ensue, producing aberrations within key cellular pathways and trigger cell death. [4, 33] These papers demonstrated large therapeutic indexes for PARP inhibitors in HR-deficient cells, which it was hoped could be leveraged into both extremely effective and well tolerated treatment options in this population at elevated risk for a number of malignancies. [33] Given the high incidence and mortality associated with prostate carcinoma, along with the high rate of HR deficits in metastatic CRPC (approximately 20–25% of cases), there is substantial enthusiasm for developing PARP inhibitors for prostate carcinoma.…”
Section: Need For Further Therapeutic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, DNA damage responses, and predominantly DNA repair, influence the outcome of therapy. Moreover, a substantial association of DNA repairs and drug sensitivity has been demonstrated using cell lines [12]. This indicates a more complex relationship between the efficiency of DNA repair mechanism and tumor therapy.…”
Section: Dna Mismatch Repair Systemmentioning
confidence: 99%
“…PARP inhibition exhibited significant antitumor activity in men with advanced metastatic CRPC, and deleterious germline mutations in BRCA2. Studies have also demonstrated that olaparib would have antitumor activity in sporadic cases of metastatic, CRPC with DNA-repair defects [12].…”
Section: Personalized Treatment Care In Pcamentioning
confidence: 99%